The Dividing Sword: Basil Bunting’s The Spoils - Jeffrey Twitchell-Waas (Sillages Critiques)
The late celebrity of Briggflatts has tended to subsume the body of Basil Bunting’s poetry into that poem’s themes and expectations and obscured the underlying assumptions that motivate his work. This is his extreme rejection of modernity – manifest in a money economy, the administered state and abstract thought – to which Bunting reacted by adopting an anti-humanist stance that determines both the form and content of his poetry. The basic terms of this position are preliminarily examined in a handful of early short poems, followed by a close reading of The Spoils – a poem that seems to baffle most commentators but represents Bunting’s most trenchant expression of his values and world view. Finally, the implications of this examination are brought to bear on Briggflatts itself to indicate how it is motivated by a systematic negation of the contemporary society that Bunting rejects.